Morphology of the limb, shell and head explain the variation in performance and ecology across 14 turtle taxa (12 species). (4th September 2021) - Butterfield, Taggert G; Herrel, Anthony; Olson, Mark E; Contreras-Garduño, Jorge; Macip-Ríos, Rodrigo
Abstract: Given that morphology directly influences the ability of an organism to utilize its habitat and dietary resources, it also influences fitness. Comparing the relationship between morphology, performance and ecology is fundamental to understand how organisms evolve to occupy a wide range of habitats and diets. In turtles, studies have documented important relationships between morphology, performance and ecology, but none was field based or considered limb, shell and head morphology simultaneously. We compared the morphology, performance and ecology of 14 turtle taxa (12 species) in Mexico that range in their affinity to water and in their diet. We took linear measurements of limb, shell and head variables. We measured maximum swimming speed, maximum bite force and how often turtles were encountered on land, and we used stable isotopes to assess trophic position. We used these data to test the following three hypotheses: (1) morphology, performance and ecology covary; (2) limb and shell variables, like hand length, are correlated with swimming speed and the percentage of time spent on land; and (3) head variables, such as head width, are correlated with bite force and stable isotopes. We find support for these hypotheses and provide the first evidence that morphology influences performance and ecology in turtles in the field.